(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
Gender budgeting recognizes and provides resources to address the different needs, interests and realities of women and men in society and the underlying inequalities that arise from them. It recognizes the differential contributions of men and women in the production of goods and services, as well as in work, and takes them into account in the mobilization and allocation of resources. The article discusses the prospects of this issue in Uzbekistan.